Prenatal iron supplementation adjusted to maternal iron stores reduces behavioural problems in 4‐year‐old children - Lucía Iglesias‐Vázquez; Josefa Canals; Carmen Hernández‐Martínez; Núria Voltas; Victoria Arija (Wiley, 2024)
Abstract Prenatal iron supplementation improves children's health and cognitive performance, but few studies explore behavioural development. This study assessed the effects of adjusting prenatal iron supplementation to maternal iron stores during early pregnancy on children's behavioural problems. Randomized controlled trial conducted in Tarragona (Spain) involving 230 nonanaemic pregnant women and their children after a 4‐year follow‐up. Based on haemoglobin (Hb) levels before gestational week (GW) 12, women receive different iron doses: those with Hb = 110-130 g/L were randomized to receive 80 or 40 mg/day and those with Hb > 130 g/L were randomized to receive 20 or 40 mg/day. Maternal iron stores at GW12 were classified using serum ferritin (SF) as low (SF < 15 µg/L), normal (SF = 15-65 µg/L), and normal‐high (SF > 65 µg/L). Children's behaviour was assessed by parents using the Child Behaviour Checklist for ages 1.5-5 years and the Behaviour Rating Inventory of Executive Function‐Preschool Version, and by teachers using the Teacher's Report Form for ages 1.5-5 years. Multivariable regression models were performed. Taking 80 mg/day of iron improved child behaviour when women had low iron stores but worsened it when mothers had normal-high iron stores, except for depressive and attention/hyperactivity problems. Taking 20 mg/day of iron improved behaviour only in those children whose mothers had SF > 65 µg/L in early pregnancy. Additionally, executive functioning improved at high doses of prenatal iron when maternal baseline SF < 15 µg/L. Adjusting prenatal iron supplementation to both maternal baseline Hb levels and iron stores reduces behavioural problems in 4‐year‐old children.